Principles of Islamic Communication Islamic Religious Instructors in Fostering the Morals of Youth Mosques in the City of Tanjungbalai - Rubino; Kaya Arfah (INFOKUM, 2022)
KIslamic communication as a process of conveying messages or information from communicators to communicants by using the principles and methods of communication contained in the Qur'an and Hadith. In Islamic communication activities, communicators must be guided by the principles of Islamic communication, namely qaulan sadidan (true, not lying); qaulan baligha (straightforward, effective); qaulan ma'rufa (kind and polite words); qaulan karima (respect, respect); qaulan layina (gentle);dan qaulan maysura (easy to understand). This research is categorized as qualitative research. Because this research explains the phenomenon that occurs when Islamic religious instructors carry out moral development for mosque youth in Tanjungbalai City and collects data obtained from research informants and is developed in the results of research and discussion. According to Kirk and Miller, qualitative research is a certain tradition in social science that fundamentally depends on observing humans in their own fields and relating to these people in their language and in their terms. The results of the study show that the efforts made by Islamic religious instructors in fostering adolescent moralsAlmuttaqin S Dengki mosqueinTanjung Balai Citynamely holding regular lectures, coachingmosque youth, and facilitating religious activities. Factors that hinder Islamic religious instructors in fostering adolescent morals are the existence of groupings in adolescents, the influence of technological sophistication,kdiscomfort among youth administrators of the mosque/mushollah, bthe amount of debt in payment of contributions that have been agreed upon, tsometimes there is bullying among friends, kbusy personally so did not have time to come to attend the majlisknowledge.